Respostas
respondido por:
1
x - y = 6
x + y = 7
----------------------
2x // = 13
x = 13/2 = 6.5 ****
6,5 - y = 6
-y = 6 - 6.5 =
-y = - 0,5
y = 0,5 ***
x + y = 7
----------------------
2x // = 13
x = 13/2 = 6.5 ****
6,5 - y = 6
-y = 6 - 6.5 =
-y = - 0,5
y = 0,5 ***
respondido por:
0
x - y = 6
x + y =7
-------------
2x = 13
x= 13/2
x= 6,5
6,5 - y = 6
-y = 6 - 6,5 (.-1)
y = 0,5
S=( 6.5, 0,5)
espero ter ajudado
x + y =7
-------------
2x = 13
x= 13/2
x= 6,5
6,5 - y = 6
-y = 6 - 6,5 (.-1)
y = 0,5
S=( 6.5, 0,5)
espero ter ajudado
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás